Bridging the fitness gap: Developing the capacity of PE teachers via a community empowerment model - Ilyas, Muslim Bin; Mappanyukki, Andi Atssam; Mukrim, Harvina (Universitas Muhammadiyah Magelang, 2025)
Physical Education (PE) teachers play a central role as role models for a healthy lifestyle; however, PE teachers in Gowa Regency still face challenges, including fitness levels that tend to be moderate to low, coupled with minimal understanding and application of sport recovery techniques. This condition directly affects their teaching effectiveness and overall quality of life. This community service program aimed to address these issues by enhancing their physical fitness, mastery of sport recovery techniques, and development of community-based fitness entrepreneurship skills. The program employed an interactive training methodology consisting of socialization, direct practice, and continuous mentoring. The main activities involved 45 participants from the Subject Teacher Forum (MGMP) for PE in Gowa, followed by a three-month mentoring phase at their respective schools. The material taught included structured fitness exercises and post-exercise recovery techniques such as cool down, stretching, foam rolling, and simple cryotherapy. The results of the activity showed a substantial improvement in the teachers' fitness. The average general fitness score increased by 9.07% (from 18.22 to 19.88 points), and their VO2max capacity increased by 15%. Qualitatively, complaints of post-exercise muscle soreness decreased by 30% after the application of recovery techniques. The long-term impact of this activity is also evident in the formation of the Gowa Fit Teachers Community (KGBG) as a platform for sustainability. Furthermore, approximately 25% of the participants successfully started or developed community-based fitness ventures, such as community aerobics classes or sports massage services. The program proved effective in improving physical condition and understanding of sport recovery, while simultaneously creating new economic opportunities for PE teachers in Gowa Regency.